Monitoring Perubahan Lahan Sawah dan Alih Kepemilikan Lahan di Kecamatan Ubud Berbasis Remote Sensing dan GIS - PUTU CANDRA LINDARI; NENGAH NETERA SUBADIYASA; I MADE MEGA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Monitoring Changes Of Paddy Fields and Land Ownership in Ubud District Using Remote Sensing and GIS Rapid development of tourism in district of Ubud has high impact on paddy field landuse change followed by changes of ownership of the land. This research aims to analyse the magnitude of the landuse change of the paddy field as well as changes in land ownership in Ubud from years of 2012 to 2017. The research was held on January 2017 until August 2017 in Ubud District with following stages, namely (a) the preparation of data, (b) a visual interpretation of satellite imagery, (c) on screen digitation, (d), (e) reinterpretation of changes paddy fields from 2012 and 2017, (f) the determination of the number of sample points, (g) surveys, (h) data analysis. The results showed changes in paddy field into non-agricultural land in the period of 2012-2017 as much as 260.86 ha and the highest changes on Ubud village as much as 127.14 ha. Land ownership in Ubud district is still majority owned by the local people originated from Ubud District. On the other hand, land ownership owned by local people who are not originated of Ubud District was in Petulu village, Mas village and Ubud Village. Indonesia citizen from Jakarta also owned land in the Ubud Village. Most of land are for rent and there are land for rent in cooperate with foreign citizens, such as villas located in the Ubud village.